Dystocia Due to Foetal Anasarca along with Twin Live Foetus In Doe and its Successful Management - Patil, Manjusha G; Misalwar , Lalit V.; Markendeya, Niteen M.; Hase, Pankaj B. (Animal Reproduction Update, 2022)
A seven years old full term multiparous non-descript doe and a four-year-old full term ND doe presented at different days for dystocia due to abnormally large size foetus with head of foetus cut off by local quack in one of the cases. Based on clinical and per vaginal examination it was diagnosed as dystocia due to foetal anasarca. The present case paper reports the successful management of dystocia due to foetal anasarca by caesarean section and per vaginum by traction respectively.
Keywords: C-section; Doe; Dystocia; Foetal anasarca